Quantitative Evaluation of Proteinuria with Urinalysis Test and Comparing Its Correlation with Random Spot Urine PCR and 24-Hour Urine Protein in SLE Patients: Analysis of proteinuria - Chun Ruh Ng; Yet Lin Loh; Dawan Khadijah (Indonesian Journal of Rheumatology, 2022)
Introduction: Lupus nephritis is an important concern among systemic lupus erythematosus (SLE) patients in Asia, and its mortality rate was reported to be 6 times higher compared to the general population. 24-hour urine protein collection has long been used as the gold standard test to assess proteinuria. This study aimed to assess the correlation of urinalysis test with random spot urine protein-creatinine ratio (PCR) compared with 24- hour urine protein. Methods: This was a retrospective study. The electronic medical records of all SLE patients seen in the rheumatology clinic of Hospital Sultan Ismail from 1st January 2017 to 1st January 2021 were reviewed. Patients who had urinalysis, urine protein-creatinine ratio, and 24-hour urine protein tests were identified. Data on demography, urinalysis, random spot urine protein-creatinine ratio, and 24-hour urine protein were obtained and analysed. Results: The correlation between urinalysis and 24-hour urine protein was strong (r=0.702), whereas the correlation between urinalysis and urine PCR was stronger (r=0.797). Our study also showed the correlation between random urine protein-creatinine ratio and 24-hour urine protein is strong (r=0.782). Conclusion: Urinalysis correlates well with both random spot urine protein-creatinine ratio and 24-hour urine protein, and the correlation is stronger with urine protein-creatinine ratio.